2007
DOI: 10.1091/mbc.e06-06-0532
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Clathrin in Reassembly of the Golgi Apparatus

Abstract: The Golgi apparatus is a highly dynamic organelle whose organization is maintained by a proteinaceous matrix, cytoskeletal components, and inositol phospholipids. In mammalian cells, disassembly of the organelle occurs reversibly at the onset of mitosis and irreversibly during apoptosis. Several pharmacological agents including nocodazole, brefeldin A (BFA), and primary alcohols (1-butanol) induce reversible fragmentation of the Golgi apparatus. To dissect the mechanism of Golgi reassembly, rat NRK and GH3 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 64 publications
0
36
0
Order By: Relevance
“…Loss of syntaxin-4 from the plasma membrane and its increased association in Golgi membranes would be expected to decrease effectiveness of Golgi-plasma membrane anterograde transport. Figure 3B also shows clathrin, an important mediator of export from the Golgi (46), is also trapped in MCTP-treated PAEC Golgi membranes. Figure 4 demonstrates that the trapping of Golgi tethers, SNAREs, and SNAPs is not cell type specific but also occurs in the A549 epithelial cells.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Loss of syntaxin-4 from the plasma membrane and its increased association in Golgi membranes would be expected to decrease effectiveness of Golgi-plasma membrane anterograde transport. Figure 3B also shows clathrin, an important mediator of export from the Golgi (46), is also trapped in MCTP-treated PAEC Golgi membranes. Figure 4 demonstrates that the trapping of Golgi tethers, SNAREs, and SNAPs is not cell type specific but also occurs in the A549 epithelial cells.…”
Section: Resultsmentioning
confidence: 86%
“…Additionally, because the process of membrane fusion is not dependent exclusively on SNAREs but also requires tether proteins, which are believed to act before SNARE interactions, we also investigated MCTP-induced changes in the Golgi tethers p115, GM130, giantin, and golgin 84, which play a critical role in association of coatomer protein complex I (COP-I) vesicles with the Golgi apparatus and ER-Golgi and intra-Golgi transport (4,51,52). Additionally, as transport of proteins from the trans-Golgi network is dependent on clathrin, we included clathrin in our investigations (46). Although defects in these critical mediators of vesicular trafficking through the Golgi apparatus have been described individually and have widespread effects on subcellular trafficking [as examples, mutant syntaxin-6 isoforms reduce the amount of cav-1 present at the plasma membrane in human skin fibroblasts (7), dominant negative GM130 inhibits COP-I vesicle fusion with the Golgi and decreases VSV-G cell surface trafficking (52), knockdown of GS15 largely leads to redistribution of GS28 and syntaxin-5, but not p115, GM130, and syntaxin-6 (70)], we observed that in MCTP-induced megalocytosis, all tethers, SNAREs, and SNAPs examined were trapped in the Golgi as assayed using cell fractionation and assumed a circumnuclear/perinuclear localization by immunofluorescence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Clathrin has been implicated in a number of nonendocytic functions including the maintenance of basolateral polarity involving the regulation of protein exit from the Golgi [15], and post-mitotic Golgi reassembly [16]. A number of proteins required for the maintenance of the Golgi stack are known to associate with the spindle [17] and clathrin redistribution may be a marker for their recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic cells in cytokinesis were collected 10 h after release from the aphidicolin block, pelleted, and fixed as above. The cell pellets were processed for EM as described previously (37).…”
Section: Methodsmentioning
confidence: 99%